Damage Control Resuscitation. (5th September 2018) - Cap, Andrew P; Pidcoke, Heather F; Spinella, Philip; Strandenes, Geir; Borgman, Matthew A; Schreiber, Martin; Holcomb, John; Tien, Homer Chin-Nan; Beckett, Andrew N; Doughty, Heidi; Woolley, Tom; Rappold, Joseph; et al.
Abstract: Damage control resuscitation (DCR) is a strategy for resuscitating patients from hemorrhagic shock to rapidly restore homeostasis. Efforts are focused on blood product transfusion with whole blood or component therapy closely approximating whole blood, limited use of crystalloid to avoid dilutional coagulopathy, hypotensive resuscitation until bleeding control is achieved, empiric use of tranexamic acid, prevention of acidosis and hypothermia, and rapid definitive surgical control of bleeding. Patients receiving uncrossmatched Type O blood in the emergency department and later receiving cumulative transfusions of 10 or more red blood cell units in the initial 24-hour post-injury (massive transfusion) are widely recognized as being at increased risk of morbidity and mortality due to exsanguination. Ideally, these patients should be rapidly identified, however anticipating transfusion needs is challenging. Useful indicators of massive transfusion reviewed in this guideline include: systolic blood pressure <110 mmHg, heart rate > 105 bpm, hematocrit <32%, pH < 7.25, injury pattern (above-the-knee traumatic amputation especially if pelvic injury is present, multi-amputation, clinically obvious penetrating injury to chest or abdomen), >2 regions positive on Focused Assessment with Sonography for Trauma (FAST) scan, lactate concentration on admission >2.5, admission international normalized ratio ≥1.2–1.4, near infrared spectroscopy-derived StO2 < 75% (in practice, rarely available), BD > 6 meq/L. Unique aspects of out-of-hospital DCR (point of injury, en-route, and remote DCR) and in-hospital (Medical Treatment Facilities: Role 2b/Forward surgical teams – role 3/ combat support hospitals) are reviewed in this guideline, along with pediatric considerations.